STRATEGI GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PAI DI SMA NEGERI 4 MALANG - Fauziah Nur Islamiyah; Abdul Jalil; Adi Sudrajat (VICRATINA, 2022)
The function of the religious teacher as a motivator is needed, especially if it is associated with the learning process that occurs in public schools, especially SMA Negeri 4 Malang. The purpose of this study was to determine the teacher's strategy in increasing student motivation in PAI subjects at SMA Negeri 4 Malang. This type of research is a qualitative research with a field research approach. The results of this study are in increasing students' learning motivation at SMA Negeri 4 Malang the teacher uses a special learning strategy for PAI (Islamic Education) designed to optimize student learning objectives, the first by providing ice breaking, the second often conducting competitions or competition to foster motivation, the third is to give praise and affection, the fourth is to arouse curiosity about something very important, the fifth is to give rewards or awards to students who excel as a form of how to grow motivation for students.